Terapi Kognitif Perilaku Untuk Pasien Voyourisme: Laporan Kasus Berbasis Bukti Cognitive Behavior Therapy For Voyourisme: An Evidence Based Case Report - Gunawan, Hendra; Nugroho , IGB Indro; Kusuma , Wijaya (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2023)
The problem of sexual deviance has become a social problem among the people. Several forms of sexual deviance include sexual development which results in type identity disorder, paraphilia, psychosexual dysfunction and others. voyourism becomes sexually aroused by watching an unsuspecting person undress, get naked or have sex, voyourism disorder involves voyouristic urges or fantasies or is distressed by or unable to function because of these urges. This study aims to determine the effectiveness of Cognitive Behavior Therapy to reduce symptoms in patients with Voyourism. The search method is carried out from trusted journal sources and is often used to search for scientific journals, including PubMed, Cochrane, MedlinePlus, Proquest, and Science Direct. The keywords used are "Paraphilic Disorder" AND "Cognitive Behavior Therapy" AND "Symptoms Reduction", journal publications in 2017-2022 with the type of randomized controlled trial, systematic review, meta-analysis. Human research subjects, with English option. The results of the study showed that cognitive behavioral therapy in patients with voyourism disorder has moderate effectiveness in reducing voyourism symptoms and preventing recurrences. The conclusion in this study is that cognitive behavioral therapy can be a therapy and is useful in preventing recurrence of voyourism in patients.